2019
DOI: 10.3390/ijms20143549
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Beneficial and Inhibiting Undesirable Biofilm Formation with Mangrove Extracts

Abstract: The extracts of two mangrove species, Bruguiera cylindrica and Laguncularia racemosa, have been analyzed at sub-lethal concentrations for their potential to modulate biofilm cycles (i.e., adhesion, maturation, and detachment) on a bacterium, yeast, and filamentous fungus. Methanolic leaf extracts were also characterized, and MS/MS analysis has been used to identify the major compounds. In this study, we showed the following. (i) Adhesion was reduced up to 85.4% in all the models except for E. coli, where adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Apart from the natural feature of keystones, biofilm also played an important role in regulating microbial interactions. Early evidence showed that biofilm could form in mangrove roots (Mallick et al, 2018;Glasenapp et al, 2019). Combined with the fact that endophytes were capable of forming mixedcommunity biofilms inside roots (van Overbeek and Saikkonen, 2016), we supposed a high potential of the mixed-community biofilm formation in the endosphere of the mangrove root, thereby providing a niche for intensive microbial inter-domain associations (Cai et al, 2019).…”
Section: Discussionmentioning
confidence: 83%
“…Apart from the natural feature of keystones, biofilm also played an important role in regulating microbial interactions. Early evidence showed that biofilm could form in mangrove roots (Mallick et al, 2018;Glasenapp et al, 2019). Combined with the fact that endophytes were capable of forming mixedcommunity biofilms inside roots (van Overbeek and Saikkonen, 2016), we supposed a high potential of the mixed-community biofilm formation in the endosphere of the mangrove root, thereby providing a niche for intensive microbial inter-domain associations (Cai et al, 2019).…”
Section: Discussionmentioning
confidence: 83%
“…S21A ), except for H10, H23, H25, and H30 for which bacterial survival rates were slightly lower than on non-coated PS (95%, 94%, 89%, and 90%, respectively). Although antibacterial activity has been reported for some plant phenolic compounds [ 9 , 21 , 40 , 41 ], it was also shown that these compounds could both enhance or inhibit the formation and growth of bacteria depending on the experimental conditions [ [40] , [41] , [42] , [43] , [44] , [45] ].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that a reduced number of adhered cells did not guarantee a biofilm biomass reduction. Glasenapp et al [36] observed that although sub-lethal concentrations of mangrove extracts reduced microbial adhesion to the surfaces, they stimulated EPS production with a consequent increase in biofilm biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm biomass was evaluated measuring the amount of cellular protein [36]. Briefly, two membranes for each treatment were transferred in 1 mL of phosphate buffered saline solution (PBS), and biofilm was removed from the membrane surface by 1 min vortex mixing, 2 min sonication (50% amplitude, in a water bath; Branson 3510, Branson Ultrasonic Corporation, Dunburry, CT, USA) followed by another 1 min of vortex mixing.…”
Section: Biofilm Biomass Quantificationmentioning
confidence: 99%